Review of the European Helicobacter Study Group Workshop reports (Ljubljana, 2012) - A. A. Sheptulin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To discuss the reports delivered at the International Workshop of the European Helicobacter Study Group (Ljubljana, Slovenia, 13-15 September 2012).Summary. Possible correlations of H. pylori infection with rate of various diseases development – both positive (colorectal cancer, liver diseases, Alzheimer's disease), and negative (gastroesophageal reflux disease, adenocarcinoma of the esophagus, chronic inflammatory bowel diseases, bronchial asthma) continue to be studied. Increasing resistance H. pylori to various antibiotics require the further improvement of modes of eradication therapy.Conclusion. Pathogenic and clinical aspects of H. pylori infection issue require further investigation.